2016
DOI: 10.1016/j.anorl.2016.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Long term results after cochlear implantation: Schooling and social insertion of teenagers and young adults

Abstract: On the long term the lexical level remains a relevant tool to assess the evolution of implantees. For those who do not reach a near to normal lexical level, impact on the schooling and the social insertion has to be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The percentage of CI users entering mainstream education in our study (16/37 ¼ 43%) is in line with the results of previous studies ranging from 36 to 83%, with higher percentages found in the younger age groups (5)(6)(7)(8)18,19). In German mainstream education, 94% of the CI users have learned at least one foreign language, whereas about half of the CI users in special schools for the hearingdisabled went to foreign language classes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The percentage of CI users entering mainstream education in our study (16/37 ¼ 43%) is in line with the results of previous studies ranging from 36 to 83%, with higher percentages found in the younger age groups (5)(6)(7)(8)18,19). In German mainstream education, 94% of the CI users have learned at least one foreign language, whereas about half of the CI users in special schools for the hearingdisabled went to foreign language classes.…”
Section: Discussionsupporting
confidence: 91%
“…Early identification of hearing loss and rehabilitation using cochlear implants (CI) allow bilaterally deaf children to attain appropriate language acquisition, even in patients from bilingual families (2). Many deaf children with CI may even enter normal schooling (5)(6)(7)(8). In Switzerland which has four official national languages, the Swiss Conference of Cantonal Ministers of Education issued in 2004 a new series of guidelines for foreign language instruction throughout Switzerland (9).…”
mentioning
confidence: 99%
“…1 The ideal outcomes from the use of a CI should be improvements in not only hearing, speech, and language skills but also in the recipient's quality of life. 2 Although it is difficult to evaluate the quality of life with specific indicators, several previous studies have assessed improvements in this metric after cochlear implantation in children by identifying their subsequent education and employment status, [3][4][5][6][7][8][9] as these outcomes are important components of mental and social well-being.…”
mentioning
confidence: 99%